An Analysis of Writing Competence of Class VIII Students of SMP Negeri 3 Tanjung Pinang through English Recount Text - Dinda Widianda; Nana Raihana Askurny; Seri Jelita; Fitri Noviyanti; Chindy Marselina; Keti; Grace Angela marbun (Teaching English and Language Learning English Journal, 2025)
Abstract This study aims to describe the writing competence of grade VIII students of SMP Negeri 3 Tanjungpinang through the analysis of English recount text. The method used was descriptive qualitative with data collection through interviews with English teachers and documentation of students' writing. The results showed that students' scores varied greatly, ranging from 10 to 100. A total of 31.8% of students obtained very good grades (90-100), which shows that some students have mastered the material well. However, 36% of students were in the less and very less categories, indicating that many students had difficulty in writing recount texts. Factors influencing the difference include learning style, motivation, as well as the support of the learning environment at home. Teachers also revealed that learning tends to be monotonous with minimal use of visual media and collaborative activities. This finding indicates the need to apply more varied and contextualized learning methods, such as genre-based approaches, the use of visual media, and active learning. In addition, special attention and remedial programs for students with low scores are needed to improve their writing competence. Synergy between teachers, schools and parents is also important to create a supportive and inclusive learning enviromental.